Woody Plants of Ulu Muda Forest Reserve Kedah, Malaysia - RAHMAD, Zakaria; ROSAZLINA, Rusly; AKOMOLAFE, Gbenga Festus (Journal of Tropical Biology & Conservation (JTBC), 2024)
The woody plants species inventory and diversity of primary, old secondary and secondary forest patches of Ulu Muda Forest Reserve (UMFR), Kedah, Peninsular Malaysia were assessed in this study. This was done to understand the current status of the forest towards ensuring proper conservation plans. Plants with diameter at breast height of not less than 10 were identified and enumerated within 10m radius (both left and right) of a 1500m transect laid at each site. Two hundred and thirty-five (235) plant species belonging to 56 families and 144 genera were enumerated in all the sites. The percentage composition of lianas (14.53%) was found to be very minimal to tree species (76.49%) which denotes the health status of the forest. Polyalthia jenkensii, Spondias cytherea and Intsia palembanica were the most common plants in the three sites. The Shannon diversity index of all the sites was observed to be greater than 2, which shows the high diverse nature of the forest despite some past disturbances. The old secondary forest patch was reported to have recuperated over the years due to its highest diversity indices.